A Mechanical Model of Heart Valves with Chordae for in Silico Real-Time Computations and Cardiac Surgery Planning - GAIDULIS, Gediminas; KAČIANAUSKAS, Rimantas; Kizilova, Natalya; ROMASHOV, Yury (Engineering Transactions, 2018)
In this paper, a two-dimensional (2D) model of the dynamics of mitral valve with chordae is developed based on in vivo data of the periodical motion of the valve leaflets digitized from the ultrasound imaging. The chordae are considered as viscoelastic springs described by the five-element rheological model. The model allows fast numerical computations of forces in the chordae and leaflets at different locations of the chordae of a different order. It can be used in real-time computations of the patient-specific geometry for optimal surgery planning when the mitral valve insufficiency is associated with broken chordae, and neochordae implantation is needed.